Praktikalitas buku teks pelajaran materi teori kinetik gas dan termodinamika berbasis CTL dan literasi lingkungan untuk siswa SMA kelas XI - Rahma Tilla Dwi Lestari; Desnita Desnita; Asrizal Asrizal; Yenni Darvina (Universitas Negeri Padang, 2020)
The current physics learning process is still not in accordance with the expected conditions, because students are only able to understand the concepts, and have not been able to apply physics learning into daily. The solution of this problem is to use textbooks based on contextual learning and environmental literacy. This study aims to determine the level of practicality of textbooks on kinetic gas theory and thermodynamic materials based on contextual learning and environmental literacy for senior high school students in grade XI. The type of research used in this study is Research and Development (R&D) Sugiyono design. In evaluating the practicality according to the teacher and students consists of 4 components and 37 items assessed aspects. The data analysis technique used is descriptive statistical analysis consisting of practicality analysis. The results of the practicality analysis of 1 teachers with an average value 95,43 and 35 students with an average value 88,88 categories are very well. The conclusion is that the textbook of kinetic gas theory and thermodinamycs based on contextual learning and environmental literacy for senior high school students in grade XI is practically used with a very well practicality level. So, the textbook is feasible to use when learning.